Affine extensions of the Petersen graph and 2-arc-transitive graphs of girth 5 - Pasechnik, Dmitrii V. (2013)
Let Qn denote the set of the flag-transitive geometries with the diagram. We construct examples of finite Qn-geometries for any n>= 2. This allows us to obtain new examples of finite 2-arc-transitive graphs of girth 5, containing Petersen subgraphs. Using coset enumeration, we classify all Q2-geometries.